Pengaruh Bimbingan Kelompok Teknik Diskusi untuk Mengurangi Kejenuhan Belajar Al-Qur’an pada Santri - Muhammad Faizin; Anik Khoirul Umah (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2025)
This study aims to determine the effect of group guidance with group discussion techniques to reduce the saturation of learning the Koran for students Attanzil Bojonegoro. This study used a quantitative experimental method with a pre-experimental research design. The population of this research is 30 students. The sampling technique used in this research is purposive sampling. Researchers used a data collector in the form of a Likert scale with 4 alternative answer choices namely SS, S, TS, STS. Validity test obtained valid item data as many as 28 items and 3 items failed. While the reliability test with alpha cronbach technique with SPSS 29.0 and obtained a reliability value of 0.894. Because this data is parametric, quantitative analysis uses an assumption test, namely the normality test and homogeneity test. In carrying out the analysis, the analysis uses the SPSS 24.0 computer with the T test formula. The research location was carried out in the Attanzil Bojonegoro Islamic Boarding School area with a research focus on Atanzil students whose saturation in learning the Koran is high and currently. In the research results it is known that the results of the post-test have a decrease in value from the results of the pre-test before being given treatment. From the results of the normality test, it can be seen that the pretest value is 0.552 > 0.05 and the sig posttest value is 0.552 > 0.05, so it can be concluded that the data obtained from the pretest and posttest are normally distributed. Homogeneity test, obtained a sig value of 0.346 > 0.05, it can be concluded that the data obtained from the pre-test and post-test are homogeneous data. The correlation value was -0.534 and the magnitude of the P-Value coefficient (0.112) > 0.05 showed that the correlated pre-test and post-test data were not significant. and the results of the T test sig.(2-tailed) value is 0.000 <0.05, so there is a significant difference in the saturation of learning the Koran before and after being given group guidance on discussion techniques. reduce the saturation of studying the Koran attanzil Bojonegoro students.